Du livre à l’information : un tournant historiographique - Jérôme Lamy; Johann Petitjean (Cahiers d’histoire.)
‌Can the early modern society be understood as the first information society? The worlds of the written word have been considerably transformed historiographically in the last thirty years. This paper proposes a synthesis of the main advances in this field. It focuses mainly on three contemporaneous aspects, or debates. The first, which is the oldest, concerns the so-called 'revolutionary' dimension of printing, and questions in a new way this material, social and cognitive disruption. The second aspect departs from the classical perspectives on the history of publishing, and aims to show how the history of the printed book, first, and then that of reading, were based on successive paradigm shifts that have contributed to the growth of the interest in 'information'. Recent works on the dissemination of news and the information infrastructures that support these flows confirm the hypothesis of the emergence of a first information society during the early modern age. We will insist in particular on their methods, which invite to decompartmentalize in a profitable way several fields of historical research. The third and last debate concerns the finest scriptural materials, examined from the most discrete markers of thought as well as the process, modern, of progressive diversification of the supports during the period. Their study allows us to better understand the way in which early modern documents were included in the labile structures of a society great consumer of information under its various forms: handwritten or printed books, handwritten or printed newsheets, correspondences, etc.; a society great consumer of documents, and paper.